Analysis of the Implementation of Audio Visual Media in English Instruction at MTs Negeri 1 Banggai - Haluti, Armin; Arrasul, Abdul Rabbi; Tiara Dewi, Aisyah; Mukmin (BABASAL English Education Journal, 2025)
The purpose of this research is to analyze the use of audio-visual media in teaching English at MTs Negeri 1 Banggai. This study uses a qualitative research method with the subjects being students and teachers of English at MTs Negeri 1 Banggai. The research findings show that: 1) Students pay attention well in class, become more active, and often answer the teacher's questions; 2) The majority of students are more interested in the use of audio-visual media in their classroom activities; 3) Teachers understand teaching using audio-visual media because they have been using it for a long time and are accustomed to it. Audio-visual media has strengths and weaknesses: its strength lies in making teaching and learning activities easier to understand for students and helping teachers explain material more effectively. The weaknesses include a high dependence on electricity and the significant amount of time required to set up the audio-visual media in the classroom.